Butir-Butir Nilai Pancasila Dalam Kajian Tafsir Mudhu’iy - Ahmad Dibul Amda; Ratnawati Ratnawati; Mirzon Daheri (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2020)
The attitude opposing Pancasila on one hand rests upon the Qur’an as the legal basis for the people and on the other hand is a consistently hot discourse. The foregoing makes it essential to study the relevance of Pancasila and the Qur’an. The researchers examine the Qur’anic viewpoint on Pancasila by examining its relevance to the values of Pancasila’s points. This library research is descriptive qualitative. The researchers use the maudhu'iy tafsir approach in elaborating Qur’anic verses to see their compatibility with Pancasila. Maudhu'iy's interpretation begins by collecting verses related to the problem, analyzing their meanings so that they come to a conclusion. From the research, it can be understood that Pancasila and the Qur’an have the same intentions and meaning relationships. In principle, Pancasila is the Islamic teaching in the Qur’an. This conclusion is indicated by the 45 points of Pancasila’s values in that all of which have relevant meanings to the Qur’an